2016
DOI: 10.1159/000460297
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lymphocyte-Associated Cytokine Concentrations Change More Rapidly over Time in Multiple System Atrophy Compared to Parkinson Disease

Abstract: Objective: Chronic inflammatory processes contribute to the eventual death of motor neurons and the development of symptoms in both idiopathic Parkinson disease (PD) and multiple system atrophy (MSA). Given the faster rate of progression and more severe symptoms associated with MSA, we hypothesized that markers of inflammation would be more evident in the peripheral blood of MSA than PD patients, and that evidence of this inflammation might assist early diagnosis of MSA versus PD. Methods: We performed multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…8,9 Our group has studied the peripheral immune system in PD neurodegeneration by using LPS rat models, 10,11 glial cells, 12,13 and patient cerebrospinal fluid and blood. 14,15 Results from these investigations indicate that an adaptive immune response contributes to progression and supports the rationale for using an immune-modulatory therapy such as mesenchymal stem cells (MSCs). MSCs have been studied in multiple PD animal models, [16][17][18] and the potential benefit relies primarily on paracrine actions, exosomal activity, and modulation of host immune cells.…”
Section: Keymentioning
confidence: 79%
“…8,9 Our group has studied the peripheral immune system in PD neurodegeneration by using LPS rat models, 10,11 glial cells, 12,13 and patient cerebrospinal fluid and blood. 14,15 Results from these investigations indicate that an adaptive immune response contributes to progression and supports the rationale for using an immune-modulatory therapy such as mesenchymal stem cells (MSCs). MSCs have been studied in multiple PD animal models, [16][17][18] and the potential benefit relies primarily on paracrine actions, exosomal activity, and modulation of host immune cells.…”
Section: Keymentioning
confidence: 79%
“…The focus of this study is upon a relatively rare condition, Multiple System Atrophy (MSA) which was once thought to be a variation of Parkinson's Disease and had previously been described as the Shy-Drager syndrome but is now known to be a separate disease entity from Parkinson's. [23][24][25][26][27][28][29][30] . Typically in response to patient need there are self-help generated NGO's and there are now 37 MSA Trust support groups around the UK, reflecting the changing pattern of MSA and the Trust is celebrating its 20 th anniversary.…”
Section: The Micro: Multiple System Atrophy (Msa)mentioning
confidence: 99%
“…23 However, other studies have highlighted changes in the widening understanding of Parkinson type illnesses. [25][26][27][28][29][30] They stated that aside from idiopathic Parkinson syndrome, there are a number of other atypical Parkinsonian syndromes: Dementia with Lewy Bodies (DLB), Progressive Supranuclear Palsy (PSP), Cortico basal Degeneration (CBD) as well as Multiple System Atrophy.However, whilst DLB is relatively a common disease, a prevalence of 0.4% (400 cases per 100,000 persons) the later studies found that MSA and PSP have a prevalence of between 5 to 10 per 100,000 persons respectively, [23][24][25][26]29,30 virtually doubling the estimates of MSA a decade earlier 23 which mirrors the growing number of MSA Trustsupport groups across the UK.…”
Section: The Micro: Multiple System Atrophy (Msa)mentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of TNFα in degenerating regions suggests that this potent pro-inflammatory cytokine is a mediator of neuronal injury. Furthermore, markers of inflammation such as serum T-lymphocyte-associated cytokine concentrations give evidence of immune mechanisms contributing to PD and MSA disease progression [73]. The pathobiological effects of TNFα in neurodegeneration and, in particular, in PD have been critically reviewed recently [17].…”
Section: Introductionmentioning
confidence: 99%